KINERJA DAN PERANAN SEKTOR PERTANIAN DALAM PEMBANGUNAN EKONOMI KABUPATEN BLORA - WIWIT RAHAYU (Universitas Sebelas Maret, 2013)
The aims of this research are to analyze performance and role of agricultural sector and subsector in economic development of Blora regency. This research used secondary data. The analysis method are descriptive and Klassen Typology Approach. The results of this research shows that performance of the agricultural sector in Blora regency during the 2005-2009 views that agricultural sector gives the largest average contribution (53.99%) among other economic sectors, but the growth rate ranks seventh among nine economic sectors in Blora regency with anaverage growth rate of 4.26%.